Assessment of gut microbiome variations in the mother and twin infant of captive white-handed gibbons (Hylobates lar) reveals the presence of beneficial and nonpathogenic bacteria - Badrul Munir Md-Zain,; Siti Hajar Azmi,; Roberta Chaya Tawie Tingga,; Millawati Gani,; Mohamad Khairulmunir,; Abd Rahman Mohd-Ridwan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The white-handed gibbon (Hylobates lar) is one of the three Hylobatidae species found in the Peninsular Malaysia region. Studies on primate gut microbiota have yet to be conducted in Malaysian Hylobatidae, but previous studies have covered Cercopithecidae. Knowledge of the gut microbiota of endangered captive Malaysian Hylobatidae primates is important for health assessment and conservation management. Thus, the main objective of this study was to determine the gut microbiota profile of captive white-handed gibbons using the metabarcode 16S rRNA gene. Two H. lar fecal samples collected from the mother and twin infant at Zoo Melaka were used for DNA extraction. Next-generation sequencing (NGS) of the 16S rRNA gene was performed. The NGS data were analyzed on the basis of amplicon sequence variation. The gut microbiota of H. lar was dominated by phylum Firmicutes and Bacteroidota because of their important roles in fermentation and nutrient assimilation from plant-based food sources. Predominance of genus Prevotella in the gut microbiota of H. lar indicates that the captivity condition causes the gut microbiota of gibbons to resemble that of humans and associates with fiber-rich diets. Variation in the bacterial community profile between the mother and the infant indicated differences in dietary adaptations and physiological state. This study can be used as an indicator of gibbon health levels through gut microbiome screening and can be used when considering Malaysian primate health welfare and captive management.